PENERAPAN SYARI’AH ISLAM DI BRUNEI DARUSSALAM; ANTARA IDENTITAS DAN REALITA SERTA RESPON DUNIA - Fadila Syahada; Efendi Efendi (Hadharah: Jurnal Keislaman dan Peradaban, 2021)
Brunei Darussalam is a small country with an area of ± 5,765 km2 with the capital city Bandar Seri Bengawan. The Sultanate of Brunei has been in existence since the 15th century AD, passed down from one sultan to another as head of state and head of government. His Majesty the Sultan is advised by several assemblies in a cabinet of ministers, even though he is actually the controller of the highest government. After Brunei's independence in 1984, Brunei was led by Sultan Hasanul Bolkiah Mu'izaddin Wadaulah the 19th sultan. Since 1991 the Sultan has implemented MIB (Melayu Islam Beraja or the Malay Islamic Kingdom) as the state ideology, the goal is for the people to be loyal to their king, carry out the teachings and Islamic law and make it a way of life associated with the characteristics and characteristics of the true Malay nation. Brunei Darussalam is a country that is thick with Islamic culture in various aspects, from social, economic, educational, and other aspects. In October 2013 the government of Brunei Darussalam announced the nationalization of Islamic sharia law regardless of religion on May 1, 2014. The Islamic Sharia law applies to anyone without exception and has received several responses from various groups.